Apakah Pendidikan Lingkungan Merupakan Faktor Utama Pembentuk Perilaku Lingkungan pada Masyarakat di Negara Berkembang? - Nova - Ulhasanah (Dampak, 2019)
Environmental education in developed countries is currently being intensively developed to increase the environmental awareness of the community in order to achieve sustainable development. But for developing countries like Indonesia, is environmental education the most urgent thing to do first to improve the successful implementation of environmental management system? This paper presents an analysis of social aspects related to the environmental behavior of a society, which is about the importance of the "environmental education" factor for people in developing countries in general, in Indonesia specifically. In addition, other factors that form the environmental behavior of the community and their relationships with one another are also discussed. The topic chosen to represent environmental behavior in this paper is the community's environmental awareness for the waste management system in Padang, West Sumatra, Indonesia. This study uses structural equation modeling (SEM) (which consists of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA)) to investigate the environmental behavior of the community represented by 609 respondents living in the Padang city. The results of the study show that environmental education factor is ranked 3rd out of 8 determinants of the formation of environmental behavior in society, namely after the factors of "government role" and "law enforcement". This research is expected to be able to provide information to various stakeholders where providing environmental education to the community has not been able to effectively change the environmental behavior of the community if the government's role in making a good environmental management system and strong law enforcement have not been carried out.